Reading the movies : twelve great films on video and how to teach them - Costanzo, William V. (Urbana, Ill. : National Council of Teachers of English, 1992)
Provides an overview of the film genre and illustrates how traditional textual analysis can be used to understand a film's themes.
Includes bibliographical references (p. 194-199).
Includes filmographies.
Young Adult
Keywords: Film criticism; Motion pictures and literature; Motion pictures -- Philosophy; Motion pictures -- Study and teaching; Motion pictures -- Philosophy; Motion pictures -- Study and teaching